2020
DOI: 10.3389/fimmu.2020.615536
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Promote Intracellular Bactericidal Activity in Head Kidney Macrophages From Turbot (Scophthalmus maximus L.) via Hypoxia Inducible Factor-1α

Abstract: Short-chain fatty acids (SCFAs) are mainly produced by microbiota through the fermentation of carbohydrates in the intestine. Acetate, propionate, and butyrate are the most abundant SCFA metabolites and have been shown to be important in the maintenance of host health. In this study, head kidney macrophages (HKMs) were isolated and cultured from turbots. We found that the antibacterial activity of HKMs was increased after these cells were incubated with sodium butyrate, sodium propionate or sodium acetate. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…In line with our finding, butyrate was shown to improve the killing ability of macrophages via HIF-1a activation (46). However, while we propose that acetate does so by modulating glycolysis and NO production, butyrate seems to activate HIF-1a through inhibition of histone deacetylase (HDAC) leading to increased activity of lysozymes, which boost bacterial killing (46). Another study showed that butyrate inhibits HDAC3 activity, leading to reprogramming during the monocyte-to-macrophage differentiation, ultimately resulting in enhanced production of antimicrobial peptides and high bactericidal activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with our finding, butyrate was shown to improve the killing ability of macrophages via HIF-1a activation (46). However, while we propose that acetate does so by modulating glycolysis and NO production, butyrate seems to activate HIF-1a through inhibition of histone deacetylase (HDAC) leading to increased activity of lysozymes, which boost bacterial killing (46). Another study showed that butyrate inhibits HDAC3 activity, leading to reprogramming during the monocyte-to-macrophage differentiation, ultimately resulting in enhanced production of antimicrobial peptides and high bactericidal activity.…”
Section: Discussionsupporting
confidence: 92%
“…In parallel, acetate relied on NLRP3 inflammasome to increase IL-1b secretion which enhanced NO production in an autocrine manner, leading to bacterial killing (Figure 7). Despite the described role of SCFAs to improve the killing ability of macrophages, the mechanisms of action are only described for butyrate (16,(42)(43)(44)(45)(46)(47). In line with our finding, butyrate was shown to improve the killing ability of macrophages via HIF-1a activation (46).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Macrophages executed the basic role of phagocytosis and immune system motivation ( 106 ). The activated macrophages could be mainly characterized as canonical M1 and M2 types, which were in charge of the pro- and anti-inflammation responses, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As well as providing energy for colonic cells important for gut barrier integrity, SCFAs have emerged as energy substrates for colonic and liver cells and as signalling molecules influencing a range of metabolic and physiological pathways in the liver, brain, kidney, and the immune system [3,9]. Additionally, due to their low pH, SCFA are critical in preventing the colonization of pathogenic microbes [10].…”
Section: Introductionmentioning
confidence: 99%